Chemokines, chemokine receptors and atherosclerosis - John, A; Channon, K; Greaves, D (2005)
Atherosclerosis is the leading cause of morbidity and mortality in Westernized societies and is the underlying basis of myocardial infarction, stroke, and peripheral arterial disease (Libby, 2002). Atherosclerosis is a multifactorial disease associated with a number of genetic and environmental risk factors. However, it has become increasingly evident that inflammation plays a prominent role in both the initiation and the progression of atherosclerotic lesion development as well as in the complications related to plaque destabilization and rupture (Ross, 1999). Early atherosclerotic lesions consist primarily of monocyte-derived macrophages and T-cells (Stary et al., 1994), but these cells persist even in advanced lesions. Given the complexity of the inflammatory processes involved in disease pathogenesis, enormous amounts of research have been directed towards identifying the key mediators of this inflammation so that new targets for therapeutic intervention can be discovered. This brings us to chemokines. Chemokines play essential roles in inflammation and disease (D'Ambrosio et al., 2003; John and Lukacs, 2003; Proudfoot et al., 2000; Sheikine and Hansson, 2004). This family of inflammatory mediators has diverse roles in both immune and inflammatory responses, including regulation of cellular recruitment, activation, and differentiation (Gerard and Rollins, 2001). Given the importance of chemokines in the regulation of inflammatory processes, numerous strategies have been devised to modulate chemokine-receptor interactions in an attempt to identify novel therapeutic candidates for intervention in inflammatory disease. © 2005 Elsevier Inc. All rights reserved.